Effects of vitamin D supplementation on circulatory YKL-40 and MCP-1 biomarkers associated with vascular diabetic complications: A randomized, placebo-controlled, double-blind clinical trial. Issue 5 (September 2019) - Omidian, Mahsa; Mahmoudi, Maryam; Javanbakht, Mohammad Hassan; Eshraghian, Mohammad Reza; Abshirini, Maryam; Daneshzad, Elnaz; Hasani, Hossein; Alvandi, Ehsan; Djalali, Mahmoud
Abstract: Aim: Diabetic patients predispose to vascular diseases such as nephropathy, and retinopathy. Poor adherence to medical treatment and dietary recommendations in uncontrolled diabetes leads to vascular damages. Vitamin D has been extensively studied and found to be protective against diabetes mellitus. YKL-40 and Monocyte chemoattractant protein-1 (MCP-1) are considered to exert crucial role in diabetes and its complications. Therefore, this study was designed to investigate effects of vitamin D supplementation on serum levels of YKL-40 and MCP-1 involved in the development of diabetic complications. Methods: For 12 weeks, 48 type 2 diabetic patients enrolled in the trial and randomly were divided into two groups (n = 24 per group), receiving one of the following: 100 μg (4000 IU) vitamin D or placebo. Before and after intervention, serumYKL-40, MCP-1, insulin, IL-6, TNF-α, 25- (OH) vitamin D and HbA1c were measured. Results: Our results revealed that serum levels of 25 (OH) vitamin D significantly increased in vitamin D group (p < 0.001). Vitamin D supplementation also significantly reduced serum YKL-40 levels (−22.7 vs. −2.4 ng/ml; (p-value = 0.003)). There was a significant decline in MCP-1 concentration in intervention group at the end of the study (−45.7 vs. −0.9 pg/ml; (p = 0.001)). Furthermore, there was a significant decrease in IL-6, fasting insulin and HOMA-IR in intervention group after 3 months supplementation. Conclusions: Daily vitamin D supplementation effectively reduced circulatory YKL-40 and MCP-1 levels in patients with type-2 diabetes and vitamin D deficiency. Vitamin D might contribute in reducing diabetic complications via modulating YKL-40 and MCP-1 signaling pathways.